HOUT-14. PROGNOSTIC IMPACT OF FIRST PSEUDOPROGRESSION ON MRI IN GLIOBLASTOMA, AN 11 YEARS EXPERIENCE FROM A CANADIAN UNIVERSITY CENTER. (11th November 2019) - Zeidan, Elie; Assad, Anis; Letourneau Guillon, Laurent; Belanger, Karl; Lemieux Blanchard, Emilie; Lemieux, Bernard; Bahary, Jean-Paul; Roberge, David; G Masucci, Laura; Menard, Cynthia; Lambert, Carole; Moumdjian, Robert; et al.
Abstract: BACKGROUND: In glioblastomas (GBM) patients the first post-radiation MRI is usually difficult to interpret given the post-radiotherapy enhancement and possible pseudo-progression which is present in almost 50% of the patients. METHODS: We retrospectively analyzed all patients with GBM treated between 2006 and 2017 at the CHUM (SARDO database). If the first brain MRI done within 3 months after the systemic treatment showed progression of contrast, these patients were considered pseudoprogressors (PsP) while the patients who had stable or response to treatment were the non-progressors (nP). If progression persisted in subsequent MRI with a change of treatment within 6 months, they were considered early progressors (eP). If subsequent MRI improved or was stable, they were classified as nP (or true pseudo-progression). RESULTS: In our cohort of 470 patients with GBM, 57.7% were nP and 42.3% were PsP after the first post-treatment imagery. The median follow-up was 10 months. The nP had a longer mOS 15.3m vs 11.3m, p < 0.001, regardless of subsequent evolution. After the second assessment, 67.8% of PsP patients were then considered as eP and 36.4% of nP patients also progressed within 6 months. The nP either after the first or second evaluation had the same mOS (19.9m vs 18.3m), just like the eP (9.3m vs 8.6m), independently of the subsequent treatment. No demographic, molecular or clinical factor predicted PsP, except for tumor size (> 5cm, p=0.024). PsP incidence was similar between 2006–2011 (PsP 57.8%) and 2012–2017 (42.2%). The 1y OS with pseudo progression at the first MRI was 39.7% vs 54.8% with no progression (p=0.001) which has a meaningful impact for the patient. CONCLUSION: Pseudo-progression is frequent (42%) in glioblastoma and predicts a poorer prognosis with 1y OS of 39, 7%. In fact, PsP patients have more than two-thirds chance to progress precociously.